The effectiveness of PVD installation in bauxite residue soil by using Plaxis 2D for settlements analysis - Noor Aini Othman, 1982-, author 620873; Nor Zuraraihetty Mohd. Yunus, supervisor 610460; Fakulti Kejuruteraan. Sekolah Kejuruteraan Awam 619085 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Thesis (Sarjana Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2018